2021
DOI: 10.1021/acs.jpca.1c06155
|View full text |Cite
|
Sign up to set email alerts
|

Considering Density Functional Approaches for Actinide Species: The An66 Molecule Set

Abstract: The importance of spin−orbit effects on the predictions of energetic properties of actinide compounds has been considered for 18 different density functionals, comparing the spin−orbit and non-spin−orbit ("standard") forms of density functional theory (DFT). A set of enthalpies of formation for 66 small actinide (Th−Am) compoundsthe An66 set, for which experimental data are availablehave been investigated. The set includes actinide halides, oxides, and oxohalides in the general form AnO m X n , where n = 0−6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…[19][20][21][22][23] These systems may have strong multireference (MR) character due to near-degenerate orbitals, 24 which cannot be accurately accounted for in DFT due to its single-reference (SR) description of the wavefunction. 25 Although benchmarking studies [26][27][28] can be used to identify the best density functional approximation (DFA) to yield accurate energetic properties for a chosen class of material, the choice of DFA depends strongly on the system of interest and cannot be determined a priori in VHTS where most materials have yet to be characterized. 29,30 Moreover, an imbalanced treatment of systems that have weak or strong MR character can be expected to undermine the data delity and bias the candidate materials recommended by chemical discovery efforts.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] These systems may have strong multireference (MR) character due to near-degenerate orbitals, 24 which cannot be accurately accounted for in DFT due to its single-reference (SR) description of the wavefunction. 25 Although benchmarking studies [26][27][28] can be used to identify the best density functional approximation (DFA) to yield accurate energetic properties for a chosen class of material, the choice of DFA depends strongly on the system of interest and cannot be determined a priori in VHTS where most materials have yet to be characterized. 29,30 Moreover, an imbalanced treatment of systems that have weak or strong MR character can be expected to undermine the data delity and bias the candidate materials recommended by chemical discovery efforts.…”
Section: Introductionmentioning
confidence: 99%
“…TMCs may have strong multireference (MR) character due to near-degenerate orbitals, , which cannot be accurately described in DFT due to the single-reference (SR) nature of the noninteracting wave function . In addition, most density functional approximations (DFAs) are designed and benchmarked with a focus on main group systems. As a result, “Jacob’s ladder”, which suggests that DFAs lying at higher rungs will be more accurate, holds well for organic molecules but often fails to describe performance on TMCs. ,,,, To maintain data fidelity in transition metal chemical discovery, it is vital to determine whether a system contains strong MR character and choose an appropriate method in VHTS. , …”
Section: Introductionmentioning
confidence: 99%
“…To model such materials, Density Functional Theory (DFT) has become the most widely used correlated electronic structure theory approach 8 , even though it is difficult to systematically approach exact results with the currently available density functional approximations 8,9 . In the particular case of relativistic electronic structure calculations, DFT energies may even for closed-shell species strongly deviate from experimental or accurate theoretical results [10][11][12] . This also holds for molecular properties, recently Sunaga and Saue 13 reported that the performance of DFT for parity violation energy shift (PV) calculations -a property requiring a very accurate description of the electronic wave function near the nuclei -is somewhat disappointing, with deviations to CCSD being as large as 10%.…”
Section: Introductionmentioning
confidence: 95%
“…56 Q γ pq = Re(γ pq ) + ǐIm(γ pq ) + ǰRe(γ p q) + ǩIm(γ p q). (11) in which lowercase symbols with (without) bars indicate the Kamers pairing of the original MO basis and the oneparticle reduced density matrix (1RDM) is now indicated by γ for consistency of notation with Shee et al This quaternion form can be diagonalized using the quaternion diagonalization routine provided by DIRAC and be back-transformed to complex representation by the routines provided in this module. If the original basis did not possess Kramers symmetry, the diagonalization is directly carried out in complex algebra.…”
Section: B Complex-quaternion Transformation and Diagonalizationmentioning
confidence: 99%